Selección electroquímica de compuestos orgánicos (ORTO-TOLUIDINA-TIOUREA) como inhibidores de corrosión de medio salino para protección del hierro en la ciudad de Machala. - Campoverde, Tatiana (2015)
In this paper the results of the electrochemical evaluation of two organic compounds Ortho-toluidine and thiourea are presented. This evaluation was performed by UV-visible. These compounds were tested at concentrations of 1, 5 10% (v / v), Also, the effect of immersion time of the electrode in the corrosive solution and in the presence of the different compounds was observed, were evaluated times 10 minutes, 24 hours, 48 hours, evaluation was made on a mechanical shaker at 100 rpm. The compound was present better results Ortho-toluidine.